أثر تعليم ريادة الأعمال في توجه الطلبة نحو تأسيس المشاريع الصغيرة في ليبيا "دراسة ميدانية على الطلبة الدارسين بالمعاهد التقنية العليا بمنطقة الساحل الغربي" (Al-Farooq Journal of Sciences, 2025)
This study aimed to explore the impact of entrepreneurship education on students’ orientation toward establishing small businesses in Libya. The research was conducted on a sample of 143 students from higher technical institutes in the Western Coastal region. Data were collected and analyzed using SPSS software. The findings revealed a statistically significant relationship between entrepreneurship education and students’ inclination to start their own businesses, highlighting the crucial role of such education in fostering entrepreneurial thinking. The study also demonstrated that the quality of educational content and teaching methods plays a key role in reinforcing this orientation. Conversely, institutional support and entrepreneurial incentives within the educational institutions studied had a less pronounced impact. The study underscores the importance of strengthening entrepreneurship education programs to encourage students to pursue small and medium-sized business ventures, thereby contributing to national economic development and addressing the challenges of unemployment in Libya.